(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Hospital Management System Human Resource 1 is a web-based system that automates and streamlines HR activities, including onboarding, recruiting, hiring, monitoring, and recognizing employee performance. The traditional way of using email for communication can be time-consuming and ineffective, leading to poor security measures and data loss, which can impact the daily operations of business. To address this issue, the project team developed a secure web-based system that simplifies the onboarding process and enables HR managers to track newly hired employees with ease. The system has enhanced security measures to ensure the protection of HR 1 data, eliminating the need for complex and paperwork-heavy processes. The system is designed to manage the version of HR 1 In HMS activities and aims to make managing HR 1 less challenging for businesses. By breaking the project into manageable sprints and prioritizing tasks based on feedback, the team delivered a web-based system that efficiently handles HR transactions for a hospital. This involved collaboration with HR personnel and stakeholders, quick delivery of a working system, and ongoing improvement. Then, the team determines the most effective way to address the issues and improve the Hospital Management System Human Resource 1. The project aimed to improve Hospital Management System Human Resource 1 by reducing paperwork, saving time, and ensuring data security while staffing the hospital effectively. The team developed a web-based system that efficiently monitors newly hired employees and produces timely HMS HR 1 reports with minimal effort.